Sodium Nitroprusside–Enhanced Cardiopulmonary Resuscitation Facilitates Intra-Arrest Therapeutic Hypothermia in a Porcine Model of Prolonged Ventricular Fibrillation*. Issue 4 (April 2015) - Debaty, Guillaume; Matsuura, Timothy R.; Bartos, Jason A.; Rees, Jennifer N.; McKnite, Scott H.; Lick, Michael; Boucher, François; Yannopoulos, Demetris
Abstract : Objectives: The aim of this study was to assess the effect of sodium nitroprusside–enhanced cardiopulmonary resuscitation on heat exchange during surface cooling. We hypothesized that sodium nitroprusside–enhanced cardiopulmonary resuscitation would decrease the time required to reach brain temperature less than 35°C compared to active compression-decompression plus impedance threshold device cardiopulmonary resuscitation alone, in the setting of intra–cardiopulmonary resuscitation cooling. We further hypothesized that the addition of epinephrine during sodium nitroprusside–enhanced cardiopulmonary resuscitation would mitigate heat exchange. Design: Prospective randomized animal investigation. Setting: Preclinical animal laboratory. Subjects: Female farm pigs ( n = 28). Interventions: After 10 minutes of untreated ventricular fibrillation, animals were randomized to three different protocols: sodium nitroprusside–enhanced cardiopulmonary resuscitation ( n = 8), sodium nitroprusside–enhanced cardiopulmonary resuscitation plus epinephrine ( n = 10), and active compression-decompression plus impedance threshold device alone (control, n = 10). All animals received surface cooling at the initiation of cardiopulmonary resuscitation. Sodium nitroprusside–enhanced cardiopulmonary resuscitation included active compression-decompression plus impedance threshold device plus abdominal binding and 2 mg of sodium nitroprusside at 1, 4, and 8 minutes of cardiopulmonary resuscitation. No epinephrine was used during cardiopulmonary resuscitation in the sodium nitroprusside–enhanced cardiopulmonary resuscitation group. Control and sodium nitroprusside–enhanced cardiopulmonary resuscitation plus epinephrine groups received 0.5 mg of epinephrine at 4.5 and 9 minutes of cardiopulmonary resuscitation. Defibrillation occurred after 10 minutes of cardiopulmonary resuscitation. After return of spontaneous circulation, an Arctic Sun (Medivance, Louiseville, CO) was applied at maximum cooling on all animals. The primary endpoint was the time required to reach brain temperature less than 35°C beginning from the time of cardiopulmonary resuscitation initiation. Data are presented as mean ± SEM. Measurements and Main Results: The time required to reach a brain temperature of 35°C was decreased with sodium nitroprusside–enhanced cardiopulmonary resuscitation versus control or sodium nitroprusside–enhanced cardiopulmonary resuscitation plus epinephrine (24 ± 6 min, 63 ± 8 min, and 50 ± 9 min, respectively; p = 0.005). Carotid blood flow was higher during cardiopulmonary resuscitation in the sodium nitroprusside–enhanced cardiopulmonary resuscitation group (83 ± 15 mL/min vs 26 ± 7 mL/min and 35 ± 5 mL/min in the control and sodium nitroprusside–enhanced cardiopulmonary resuscitation plus epinephrine groups, respectively; p = 0.001). Conclusions: This study demonstrates that sodium nitroprusside–enhanced cardiopulmonary resuscitation facilitates intra–cardiopulmonary resuscitation hypothermia. The addition of epinephrine to sodium nitroprusside–enhanced cardiopulmonary resuscitation during cardiopulmonary resuscitation reduced its improvement in heat exchange.